Interpretation of the emergence of a state in natural law theory - Nigmonjon Pardayevich Azizov (Zien Journals, 2023)
The article analyzes the causes and differences between theories of the origin of the state, the natural-law interpretation of the formation of the state from a scientific and theoretical point of view
Keywords: The state; he emergence of the state